ANALISIS PERSEPSI PENGUNJUNG TERHADAP FASILITAS, PROMOSI DAN DAYA TARIK WISATA DI PANTAI PASIR PADI PANGKALPINANG - Tri Utami; Nanang Wahyudin; Christianingrum Christianingrum (Jurnal Pariwisata Pesona, 2019)
Pasir Padi Beach is located in Pangkalpinang City and has the goal of being a prominent, popular and sustainable marine tourism area. The beach was once the most crowded beach visited by people in Bangka, but now, when compared with other beaches the amount of visit to Pasir Padi Beach less desirable. This study aimed to analyze how the perception of visitors about the facilities, promotions and tourist attraction offered in Pasir Padi Beach. This research was the research using descriptive analysis with a quantitative and qualitative approach. The samples were taken as many as 225 respodents using accidental sampling techniques. In this study, the independent variables consisted of facilities, promotion, and tourist attraction, while the dependent variable was perception. The instrument testing was validity and reliability testing. While the method of data analysis used was descriptive statistical analysis.The findings of this study concluded that in general the visitors' perceptions were good and interesting, especially in the tourism attraction variable, while the facility variable had many shortcomings, and promotion was very minimal so that it was the main priority in making improvements